IMPLEMENTASI MANAJEMEN HUMAS DALAM PROGRAM PARENTING, BUSINESS DAY DAN CELENGAN CINTA UNTUK SAHABAT - Firda Rizkita Nanda; Maisyaroh Maisyaroh; Bambang Budi Wiyono; Sunarni Sunarni; Firda Rizkita Nanda; Maisyaroh Maisyaroh; Bambang Budi Wiyono (Universitas Negeri Malang, 2024)
Abstract: The purpose of this study is to describe the implementation process of schooland community relationship management in parenting, business day andcelengan cinta for friends with the research location at SDI Surya BuanaMalang. This research uses a qualitative research approach and descriptiveresearch type. Sources of data obtained from interviews, observation, anddocumentation. The informants in this study were the principal, publicrelations assistant, teachers, parents and students. Data analysis was carriedout after data collection through data reduction, data display, verification andconfirmation of conclusions. The results of this study are (1) public relationsactivity planning is planned in the school's annual program meeting; (2)implementationof a parenting seminar program once a year by involving oneBahana Cita Persada Foundation. Parents day program is held routinely once aweek on Fridays by inviting parents. The business day program is held once amonth during recess with participants from class I-VI alternately. Charity Fridayis carried out voluntarily with students depositing money to the class teacher.Implementation of special donations in a situational manner, namely when amajor disaster occurs; (3) evaluation of public relations activities in parenting,business day and celengan cinta for friends programs, namely held once aweek or after program implementation; (4) the supporting factors, namely theexistence of a public relations program and systematic planning, the supportof the majority of parents, adequate infrastructure and funds, and possibleconditions of school organization. Inhibiting factors in the parenting seminarprogram, parents who come depend on the attractiveness of the seminarspeakers; (5) the school's efforts are to keep trying to make improvements andpromote as much as possible.